Protected sex with paid sexual partner among married men in Indonesia - I Gusti Ngurah Edi Putra (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Married men who are male clients of sex workers play an important role as